2017
DOI: 10.3390/s17081711
|View full text |Cite
|
Sign up to set email alerts
|

Complexation-Based Detection of Nickel(II) at a Graphene-Chelate Probe in the Presence of Cobalt and Zinc by Adsorptive Stripping Voltammetry

Abstract: The adsorptive stripping voltammetric detection of nickel and cobalt in water samples at metal film electrodes has been extensively studied. In this work, a novel, environmentally friendly, metal-free electrochemical probe was constructed for the ultra-trace determination of Ni2+ in water samples by Adsorptive Cathodic Stripping Voltammetry (AdCSV). The electrochemical platform is based on the adsorptive accumulation of Ni2+ ions directly onto a glassy carbon electrode (GCE) modified with dimethylglyoxime (DMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…4a). In previous paper, HB grade of GRC was used as an electrode substrate material for the determination of Pb(II) ions using bismuth [27] and a mixture of graphene and bismuth [24]. Tavares and Barbeira [26], observed that the harder graphite pencils (acronym H) are more useful for the electrochemical purposes, due to their smaller reduction/oxidation peak-to-peak separation (⧍E p ) and reduction/ oxidation peak current ratio (ipc/ipa) ∼1.…”
Section: Effect Of Different Grc Grade On Ergo Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…4a). In previous paper, HB grade of GRC was used as an electrode substrate material for the determination of Pb(II) ions using bismuth [27] and a mixture of graphene and bismuth [24]. Tavares and Barbeira [26], observed that the harder graphite pencils (acronym H) are more useful for the electrochemical purposes, due to their smaller reduction/oxidation peak-to-peak separation (⧍E p ) and reduction/ oxidation peak current ratio (ipc/ipa) ∼1.…”
Section: Effect Of Different Grc Grade On Ergo Modificationmentioning
confidence: 99%
“…Many graphene based sensors utilise glassy carbon as an electrode substrate material [10,24]. Conversely, glassy carbon is typically expensive, require routine polishing, and has limited lifespan [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods including spectrometry [5][6][7][8][9][10][11][12][13][14][15][16], liquid chromatography [17,18], ion chromatography [19], flame photometry [20] and electrochemical techniques [21][22][23][24][25][26], have been used for the determination of nickel in biological, food, natural water, and wastewater samples. Non-electrochemical methods have basic defects such as long analysis time, low sensitivity and expensive devices, therefore, specific pretreatment process is necessary before the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorptive stripping voltammetry has been most often utilized for trace, separate and simultaneous nickel and cobalt ions determination in various matrices as this method ensures: high sensitivity, low costs of analysis and relatively short time of measurements. For these determinations various electrodes were used to replace highly toxic mercury electrodes including: bismuth and lead film and bulk electrodes , antimony film electrodes , unmodified glassy carbon , ion exchanger‐modified carbon paste electrodes , carbon microelectrodes modified with metal film or metal microelectrode arrays .…”
Section: Introductionmentioning
confidence: 99%